Single Multiple Cross Displacement Amplification for Rapid and Real-Time Detection of Porcine Circovirus 3 - Bian, Zhibiao; Cai, Rujian; Jiang, Zhiyong; Song, Shuai; Li, Yan; Chu, Pinpin; Zhang, Kunli; Yang, Dongxia; Gou, Hongchao; Li, Chunling (Frontiers in Veterinary Science, 2021)
Since 2016, a novel porcine circovirus, PCV3, has been infecting pigs, causing significant economic losses to the pig industry. In recent years, the infection rate of PCV3 has been increasing, and thus rapid and accurate detection methods for PCV3 are essential. In this study, we established a novel probe-based single multiple cross displacement amplification (P-S-MCDA) method for PCV3. The method was termed as P-S-MCDA. The P-S-MCDA uses seven primers to amplify the capsid gene, and the assay can be performed at 60°C for 30 min, greatly shortening the reaction time. The results of P-S-MCDA can not only be monitored in real time through fluorescence signals but also be determined by observing the fluorescence of the reaction tubes using a smartphone-based cassette. This method demonstrated good specificity and the same sensitivity as qPCR, with a minimum detection limit of 10 copies. In 139 clinical samples, the coincidence rate with qPCR was 100%. The P-S-MCDA can be widely applied in PCV3 detection in laboratories or in rural areas.